PENGARUH PEMBERIAN DOLOMIT DAN PUPUK N, P, K TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) DI LAHAN GAMBUT - Leo Noza A; Husna Yetti; M Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research was carry out at the experimental garden of Agriculture Faculty, University of Riau. The aim of this research to determine the effect grant of dolomite and N, P, K fertilizers interactions on sweet corn in peat land and get the best treatment. This research was carried out using a Randomized Design Group (RDG) with 2 factors and 3 replications. The first factor use of the dolomite and the second factor is N, P, K treatment. The data were proceed with analysis of variance and Duncan’s New Multiple Range Test at 5% level. Parameters measured are plant height, stamen appears time, stigma appears time, harvest time, cob diameter, cob length without hust, cob weight without hust/sample. The result of research shown that giving of Dolomite and N, P, K fertilizers can increase growth and production on sweet corn applications of          4 ton/ha dolomite and N, P, K fertilizers (300 kg/ha Urea + 200 kg/ha SP-36        + 100 kg/ha KCl) give the best effect for cob weight without husk/sample productions on sweet corn in peat land.   Keywords : Sweet corn, peat land, dolomite, N, P, K fertilizer.